Customer support and new product development : An exploratory study - Goffin, Keith; New, Colin (Emerald Group Publishing Limited, 2001)
Customer support is an essential element in the successful marketing of many products – from domestic appliances to high-tech computer networks. Many aspects of support are strongly influenced by a product’s design and so customer support requirements should be evaluated during new product development. However, researchers have largely ignored the relationship between new product development and customer support. The current study addressed this gap by using case studies and a workshop, both conducted with leading companies, to identify how customer support is typically evaluated at the design stage and to determine the importance of this aspect of new product development. The results have implications for managers responsible for product innovation – they show the need to allocate adequate resources to integrating customer support requirements into new product develo
Keywords: After-sales service; Customer care; Design; New product development